Physicochemical evaluation of DEAE-Dx coated liposomes for long alkyl chain lipids. Issue 57 (26th May 2016) - Menon, Premanarayani; Teo, Yin Yin; Misran, Misni
Abstract : The purpose of this work was to study the potential of diethylaminoethyl dextran (DEAE-Dx) coated liposomes as drug carriers. Abstract : The purpose of this work was to study the potential of diethylaminoethyl dextran (DEAE-Dx) coated liposomes as drug carriers. Thin film hydration method was employed to prepare 1, 2-dipalmitoyl- sn -glycero-3-phospocholine (DPPC) and 1, 2-distearoyl- sn -glycero-3-phospocholine (DSPC). The critical vesicular concentration (CVC) of DPPC and DSPC was found to be 0.08% (w/v) and 0.06% (w/v), respectively. As stability is a general problem with liposomes, DEAE-Dx as a polymer was used to promote steric stabilization by coating the surface of the DPPC and DSPC liposomes. Liposomes stabilized by DEAE-Dx were superior to the corresponding non-coated liposomes. The surface behaviour of DPPC and DSPC was investigated through surface tension analysis before and after the addition of DEAE-Dx. All the liposomes were evaluated based on their particle size, zeta potential and morphology. A thirty-five day stability study shows that the particle size and zeta potential of DEAE-Dx coated liposomes were stable at room temperature. The DEAE-Dx coated liposomes were loaded with an antihistamine drug, diphenhydramine hydrochloride (DPH). The encapsulation efficiency profile shows that DEAE-Dx coated DPPC (DPPC-DEAE-Dx) liposomes have higher entrapment of DPH compared to DEAE-Dx coated DSPC liposome (DSPC-DEAE-Dx). An in vitro release experiment demonstrated DEAE-Dx coated liposomes had the best controlled release system.